Listening room compensation for wave field synthesis - Spors, Sascha; Kuntz, Achim; Rabenstein, Rudolf (2003 International Conference on Multimedia and Expo, ICME 2003, 2003)
Common room compensation algorithms are capable of dereverberating the listening room at some discrete points only. Outside these equalization points the sound quality is often even worse compared to the unequalized case. As wave field synthesis in principle allows to control the wave field within the listening area it can also be used to compensate for the reflections caused by the listening room in the complete listening area. We present a novel approach to listening room compensation which is based upon the theory of wave field synthesis and that results in a large compensated area.